Immunohistochemical evaluation of BCL-2 and KI-67 proteins in colorectal adenoma. - Abd, Areege N.; Al-Khafaji, Khitam R. (Journal of the Faculty of Medicine Baghdad, 2014)
J Fac Med Baghdad 2014; Vol.56, No .2 Received Jan .2014 Accepted Mar. 2014 Background: Development of colorectal adenocarcinoma principally occurs via the adenoma- carcinoma sequence of a multiple step process of tumor progression. This results from an accumulation of genetic changes in cells of intestinal mucosa. The use of molecular biomarkers may further aid in determining the risk of changing to carcinoma. Objectives: To evaluate the expression of Bcl-2 and Ki-67 in colorectal adenomas and correlate the observed levels with age, gender, histological type, grades of dysplasia as well as to the levels of these two markers with each other. Materials and Methods: A retrospective stu dy of fifty colorectal biopsies were selected randomly, 40 cases were with different grades of colorectal adenomas and 10 cases with normal mucosa as a control group; covering the period from 2010 till 2012. All the cases collected from the Gastroenterology and Hepatology Teaching Hospital. The biopsies were re-examined histologically and then stained immunohistochemically for Ki-67 and Bcl-2. Results: There was a significant correlation only between Ki-67 expression and grade of adenoma and there was a significant correlation between Ki-67 and Bcl-2 expression in adenoma. Also there was a significant correlation between age of the patients and histologic type. Conclusions: The assay of Ki-67 and Bcl-2 is valuable in detecting the risk of early colorectal carcinogenesis in patients with colorectal adenomas. Ki-67 expression increases with progression of the grade of adenoma while BCL-2 decrease with progression of the grade.